Pengaruh Kinerja Keuangan Terhadap Pengungkapan Sustainability Report (Studi Kasus Perusahaan Infrastruktur yang Terdaftar Di Bursa Efek Indonesia Tahun 2020 – 2022) - Azzarah, Risa Diftania; P, Ratih Hesti Utami; A, Dhea Rizky (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to determine and analyze the financial performance of infrastructure companies using sustainability reports on the Indonesia Stock Exchange for the 2020-2022 period using profitability, liquidity, leverage and activity ratios. Data collection techniques in this research use documentation and observation. The data used is secondary data in the form of financial reports and sustainability reports on infrastructure companies. The results of the research show that profitability does not have a significant influence on sustainability report disclosures, liquidity has a significant influence on sustainability report disclosures, leverage has a significant influence on sustainability report disclosures, activity does not has a significant influence on sustainability report disclosure. It can be concluded that profitability, liquidity, leverage and activity together do not have a significant simultaneous influence on the disclosure of sustainability reports for infrastructure companies listed on the IDX in 2020-2022. This is shown by the Fcount value of 2.939 with a significant value of 0.32. It can be interpreted as a significant value greater than 0.05 or 0.32 0.05. So it can be concluded that H1 is rejected, which means that financial performance (profitability, liquidity, leverage and activity) simultaneously does not have a significant influence on sustainability report disclosure.